ANALISIS PENCAHAYAAN BUATAN DI RUANG KELAS LANTAI 2 GEDUNG SEKOLAH C (SC) POLITEKNIK NEGERI SEMARANG: ANALISIS PENCAHAYAAN BUATAN DI RUANG KELAS LANTAI 2 GEDUNG SEKOLAH C (SC) POLITEKNIK NEGERI SEMARANG - Adi Setiawan; Suwarto; Sudarmono; Stefanus Santosa; Karnawan Joko Setyono; Edo Wiguna; Dian Sukma Larassati; Salmaa R.N Imansyah; Diah Wulansari Hudaya (Bangun Rekaprima, 2026)
Adequate lighting is crucial for supporting comfortable and effective classroom learning. This study evaluated the artificial lighting levels in a second-floor classroom on the C Building of Semarang State Polytechnic using a digital luxmeter. The research method used was to measure artificial lighting locally and generally. The final measurement results were compared to SNI 03-6575-2001, which requires a minimum value of 350 lux for classrooms. The measurements showed that most points had lighting values ​​below 200 lux, indicating that the lighting did not meet the standard. The low lighting levels were caused by several malfunctioning lamps and uneven light distribution due to suboptimal fixture layout and room reflectance. These findings indicate the need for lighting system improvements to enhance visual comfort and support the learning process.